2019
DOI: 10.1007/s11192-019-03092-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining how country-level science policy shapes publication patterns: the case of Poland

Abstract: This country case study describes how science policy instruments are designed to shape publication patterns and identifies the changes in researchers' productivity that can be observed over the period 2009-2016 in Poland by analysing data on 452,277 publications submitted to the country's national research evaluation system. Our analysis reveals that policy instruments used in the country's national research evaluation system, academic promotion procedures and competitive grants have increased the number of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
4
31
0
6
Order By: Relevance
“…Similarly, Butler (2003), in his study of the 1993 Australian reform that introduced undifferentiated publication counts, has shown that the number of publications in Australia significantly increased while the quality of publications significantly decreased. Quantitative results consistent with this trend have been found in Norway (Bloch et al 2016) and in Poland (Korytkowski et al 2019). Hence, "thinking with indicators" has become a central aspect of research activities, as is shown also by the studies for the Netherlands, Austria and the UK (Müller et al 2017;Salter et al 2017).…”
Section: Introductionsupporting
confidence: 67%
“…Similarly, Butler (2003), in his study of the 1993 Australian reform that introduced undifferentiated publication counts, has shown that the number of publications in Australia significantly increased while the quality of publications significantly decreased. Quantitative results consistent with this trend have been found in Norway (Bloch et al 2016) and in Poland (Korytkowski et al 2019). Hence, "thinking with indicators" has become a central aspect of research activities, as is shown also by the studies for the Netherlands, Austria and the UK (Müller et al 2017;Salter et al 2017).…”
Section: Introductionsupporting
confidence: 67%
“…Analysing the publication patterns of non-English-speaking European countries: Czech Republic, Denmark, Finland, Flanders (Belgium), Norway, Poland, Slovakia, and Slovenia [ 80 ], found that in the period between 2011 and 2014 the publication patterns were stable in West European and Nordic countries, whereas CEE countries experienced considerable changes towards more and more emphasis in English language publications in international journals. For Poland as the biggest CEE country the trend continues with regard to impact factor publications which is largely based on the strong impact of policy instruments with regard to country’s national research evaluation system, academic promotion procedures and competitive grants [ 81 ]. In October 2018 the new Law on Higher Education and Science was established in Poland (also called Science Constitution 2 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it may be concluded that in contrast to previous periods, nowadays the research productivity of business scholars in Poland is evaluated mostly through their publications registered in Scopus. This institutional change motivated Polish scholars to publish more and more in highly ranked journals, so it may be assumed that the trend identified for the period 2011–2016 [ 80 , 81 ] received some additional impetus. It translates into even more challenging situation for the older generation of Polish scholars who started their careers in communist period, where publications in Polish language were the main pattern of dissemination of their research results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evaluation systems in the Czech Republic [ 7 ] and Poland [ 8 ] favour journal articles indexed in Web of Science (WoS) and Scopus over other journal articles, books, and other types of outputs. However, SSH researchers in the Czech Republic still commonly believe that publishing in WoS journals can be at times too challenging for several reasons; whether real or perceived, these reasons include research limited to topics of local relevance, language barriers, and lack of journals in the researchers’ fields [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%